KASHMIR'S BEGGING INDUSTRY AS A MONEYMAKING VENTURE - Rutba Gulzar (CV. Radja Publika, 2023)
It was observed that beggars made up a sizable portion of the population in most urban and rural areas, regardless of the motivations for their chosen profession. They continue to grow as a fascinating phenomenon in all fields of study. This study added to the limited body of research on the topic by looking at the history and health effects of panhandling. Because of the qualitative character of the study, we used a combination of in-depth interviews, key informant interviews, and observations made by observers who were not involved in the study. Coverage included the Kashmir valley city of Srinagar. The findings revealed that some of the panhandlers have been operating for almost twenty years. They didn't see beggars as a burden on society but rather as people trying to make a living. Some people resort to begging on the streets since they have few other options for making a living because of their financial situation. Invasion into begging as a means of subsistence was prompted by chronic economic failure. Environmental annoyance and health hazards, as well as a negative portrayal of the country's human development index to foreigners, are all ways in which street begging can have an impact on public health and development. As their population keeps growing, they must keep cutting back on their labour force. As a result, the social welfare system will collapse, leaving people and ecosystems susceptible to the effects of un sustainability.